2002
DOI: 10.1901/jeab.2002.78-467
|View full text |Cite
|
Sign up to set email alerts
|

Stimulus Control Topographies and Tests of Symmetry in Pigeons

Abstract: Pigeons were tested for symmetry after A-B training under conditions designed to avoid problems that may prevent its emergence, namely the change of stimulus location in testing relative to training and the lack of requisite discrimination training. In Experiment 1, samples appeared in two locations during baseline training to minimize the impact of stimulus location. Experiments 2 and 3 included multiple-location training along with additional identity and symbolic matching training, respectively, to explicit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
79
4
8

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

6
4

Authors

Journals

citations
Cited by 51 publications
(92 citation statements)
references
References 28 publications
1
79
4
8
Order By: Relevance
“…Still, there were residual concerns about the functional matching stimuli in Lionello-DeNolf and Urcuioli (2002), so an attempt to resolve these served as the starting point for the present series of experiments. Experiments 1A, 1B, and 2 searched (albeit unsuccessfully) for symmetry in twoalternative matching with procedural variations to redress these other potential problems.…”
Section: _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ __ _ _ _ _ _ _ _ _mentioning
confidence: 99%
“…Still, there were residual concerns about the functional matching stimuli in Lionello-DeNolf and Urcuioli (2002), so an attempt to resolve these served as the starting point for the present series of experiments. Experiments 1A, 1B, and 2 searched (albeit unsuccessfully) for symmetry in twoalternative matching with procedural variations to redress these other potential problems.…”
Section: _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ __ _ _ _ _ _ _ _ _mentioning
confidence: 99%
“…However, recent follow-up work has indicated that pigeons do not seem to form acquired equivalence classes in which the behavior patterns become part of the class despite the success of the baseline training procedure (Urcuioli et al, 2006). This result may not be surprising given the difficulty of establishing stimulus equivalence in this population (e.g., Lionello-DeNolf & Urcuioli, 2002). A different outcome may occur if humans are tested using the procedure.…”
mentioning
confidence: 99%
“…Indeed, the many unsuccessful attempts to demonstrate this emergent relation (e.g., D'Amato, Salmon, Loukas, & Tomie, 1985; Dugdale & Lowe, 2000; Hogan & Zentall, 1977; Lionello-DeNolf & Urcuioli, 2002; Lipkens, Kop, & Matthijs, 1988; Sidman et al, 1982) led some to argue that language may be a prerequisite for symmetry and for equivalence more generally (see, for example, Devany, Hayes, & Nelson, 1986; Dugdale & Lowe, 1990; Horne & Lowe, 1996). However, the difficulty in finding evidence for symmetry in non-human animals is due more to methodology rather than to capability.…”
mentioning
confidence: 99%